Gambaran Kadar C-Reaktif Protein Pada Perokok Aktif - Rampo, Herniaty; Utami, Rinda Aulia; Anisa, Anisa (Institut Teknologi Kesehatan dan Sains Wiyata Husada Samarinda, 2024)
Abstract: Smoking has a detrimental impact on health and is a major factor in the occurrence of arteriosclerosis and coronary heart disease. This is because the nicotine content can stimulate platelet aggregation and Carbon monoxide (CO) can accelerate the formation of blood vessel plaques which can stimulate inflammation. Smoking has become part of the lifestyle and part of the association. Smoked cigarettes contain a wide variety of harmful chemicals such as nicotine, tar and carbon monoxide that can stimulate the inflause process. C-Reaktif Protein Is a marker of inflammation. c-reaktif protein levels can increase after trauma, infection, and inflammation. this study aims to find out how c-reaktif protein levels are described In Active Smokers. The Purpose Of The Study: to find out how c-reaktif protein levels are described in active smokers. method: this type of research is descriptive survey using 31 samples taken from 31 active smokers in rt 05 rapak rejo hamlet, kutai kartanegara. The c-reaktif protein examination using the latex agglutination method. Results: From the study conducted on Some of the respondents had a level of C-Reactive Protein <6mg/l as many as 29 respondents (93.5%).